An investigation of shoulder forces in active shoulder tackles in rugby union football - Usman, Juliana; McIntosh, Andrew S.; Fréchède, Bertrand (Elsevier, 2011)
In rugby union football the tackle is the most frequently executed skill and one most associated with injury, including shoulder injury to the tackler. Despite the importance of the tackle, little is known about the magnitude of shoulder forces in the tackle and influencing factors. The objectives of the study were to measure the shoulder force in the tackle, as well as the effects of shoulder padding, skill level, side of body, player size, and experimental setting on shoulder force. Experiments were conducted in laboratory and field settings using a repeated measures design. Thirty-five participants were recruited to the laboratory and 98 to the field setting. All were male aged over 18 years with rugby experience. The maximum force applied to the shoulder in an active shoulder tackle was measured with a custom built forceplate incorporated into a 45 kg tackle bag. The overall average maximum shoulder force was 1660 N in the laboratory and 1997 N in the field. This difference was significant. The shoulder force for tackling without shoulder pads was 1684 N compared to 1635 N with shoulder pads. There was no difference between the shoulder forces on the dominant and non-dominant sides. Shoulder force reduced with tackle repetition. No relationship was observed between player skill level and size. A substantial force can be applied to the shoulder and to an opponent in the tackle. This force is within the shoulder's injury tolerance range and is unaffected by shoulder pads.